Metode Pembelajaran Berbasis Proyek (PjBL) untuk Meningkatkan Keterampilan Menulis Cerita - M.Rizki; Ilyas Idris (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
Story writing skills are one of the essential competencies in learning Indonesian language at the elementary school level. However, in reality, many students still face difficulties in expressing ideas, organizing plots, and using language appropriately. Therefore, a learning model that can improve students’ story writing skills is needed. Project Based Learning (PjBL) was chosen because it emphasizes student activity, creativity, collaboration, and the production of tangible written works. This study employed a Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, which was carried out in two cycles. The subjects of the study were 14 third-grade students of MI Ziyadatul Iman, Jambi City. The research instruments included a story writing test, student activity observation sheets, and documentation. Data were analyzed using both quantitative techniques (average scores, mastery percentages) and qualitative techniques (student activity and reflection in each cycle). The findings showed that students’ story writing skills improved through the implementation of PjBL. The average score increased from 62.86 in the first cycle to 79.29 in the second cycle. The percentage of learning mastery also rose from 42.86% in the first cycle to 85.71% in the second cycle. In addition, students became more active, creative, and collaborative during the learning process. The implementation of Project Based Learning can therefore enhance the story writing skills of third-grade students at MI Ziyadatul Iman, Jambi City, both in terms of learning outcomes and learning activities.